2015
DOI: 10.1248/bpb.b14-00524
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Tissue Distribution, and Tentative Metabolite Identification of Sauchinone in Mice by Microsampling and HPLC-MS/MS Methods

Abstract: Sauchinone, a biologically active lignan found in Saururus chinensis (Saururaceae), exerts various biological activities against jaundice, inflammatory disease, hepatic steatosis, and oxidative injury. Despite its diverse applications, there exists some information about sauchinone's pharmacokinetics but its tissue distribution, metabolism, and tentative metabolites have not been reported yet. Thus we investigated the pharmacokinetics of sauchinone in mice using microsampling and HPLC-MS/MS methods. Sauchinone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…PCSK9, LDL-R, HMGCR, SREBP1, SREBP2, HNF1A, BIRC2, ANXA2 and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) oligonucleotide primers were purchased from Bioneer Corp. (Daejeon, South Korea). Sauchinone was isolated from the chloroform fraction of Saururus chinensis , as previously described, and confirmed by a spectroscopic analysis 32 . The purity of sauchinone was determined to be over 95% by high performance liquid chromatography using an ultraviolet detector.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…PCSK9, LDL-R, HMGCR, SREBP1, SREBP2, HNF1A, BIRC2, ANXA2 and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) oligonucleotide primers were purchased from Bioneer Corp. (Daejeon, South Korea). Sauchinone was isolated from the chloroform fraction of Saururus chinensis , as previously described, and confirmed by a spectroscopic analysis 32 . The purity of sauchinone was determined to be over 95% by high performance liquid chromatography using an ultraviolet detector.…”
Section: Methodsmentioning
confidence: 95%
“…Sauchinone isolated from Saururus chinensis has hepatoprotective, anti-inflammatory, and anti-steatosis activity 26 31 . We previously reported that sauchinone was distributed in relatively high levels in the liver 32 . Also, sauchinone inhibits hepatic steatosis mediated by the SREBP isoform, SREBP-1c, and activates AMP-activated protein kinase (AMPK) 31 .…”
Section: Introductionmentioning
confidence: 98%
“…Thus, it is meaningful to predict the potential of sauchinone–zidovudine interaction through UGT2B7. To predict the inhibitory effect of sauchinone on UGT2B7-mediated zidovudine metabolism, the following values were adjusted in Equation (1): AUC i /AUC of zidovudine was 1.52 from Table 2 , C max of sauchinone in mice plasma after oral administration of 100 mg/kg sauchinone was 1.53 μM [ 24 ] instead of [I], and K i of sauchinone for Ugt2b7 in mouse liver microsomes was 3.34 μM (our unpublished data). U.S. FDA (2012) recommends clinical evaluation of sensitive substrate if AUC i /AUC of a substrate is above 1.…”
Section: Discussionmentioning
confidence: 99%
“…First, inhibition of sauchinone or zidovudine metabolites towards UGTs was not investigated. Glucuronidation, oxidation, methylation, and dehydrogenation are involved in sauchionone metabolism [ 24 ]. Glucuronindation and reduction contribute to zidovudine metabolism [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation